Ocular Complications of Intravitreal Bevacizumab - Kanwal Zareen Abbasi, Warda Ali, Qamar Farooq, Ali Raza (Journal of Rawalpindi Medical College, 2016)
Background: To study the rate of different complications of intravitreal Bevacizumab while treating patients of different posterior segment diseases. Methods: A prospective study of 60 patients having different retinal diseases like diabetic retinopathy, wet age related macular degeneration (AMD), retinal vein occlusion (RVO),was carried out. Patients were given intravitreal Bevacizumab injection under full sterile conditions in operation theatre. The patients were rechecked during their follow up visits for the known complications of intravitreal injection i.e. subconjunctival haemorrhage, cataract, endophthalmitis, uveitis, rise of intraocular pressure (IOP), rhegmatogenous retinal detachment and vitreous haemorrhage. Results: A total of 60 patients (60 eyes), 20 males and 40 females, having age range 40-65 years, were included in the study. There were 25 eyes(41.7%) with diabetic macular edema (DME) with non-proliferative diabetic retinopathy, 20 eyes (33.3%) with proliferative diabetic retinopathy (PDR) with or without diabetic macular edema, 10 eyes with wet AMD (16%) and 5 RVO (8.3%). Post-intravitreal complications were sub-conjunctival haemorrhage in 20 eyes (19.6%), raised IOP in 3(2.9%), cataract formation in 2 eyes (1.9%), endophthalmitis in 1 eye (0.9%). No case of rhegmatogenous retinal detachment, retinal pigment epithelial detachment, retinal tear, uveitis, central retinal artery occlusion and vitreous haemorrhage was seen in our study. Conclusion: The complications are negligible if good disinfection and proper technique is observed